2022
DOI: 10.1037/apl0001000
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on the Journal of Applied Psychology in times of change.

Abstract: In the 2 years since my last Editorial, the world is arguably a different place. We have experienced a global pandemic, social justice reckoning including the Black Lives Matter movement, and increasingly pronounced political division in the United States (Dimock & Wike, 2020). Closer to home there has been increased interest and support for open science practices by professional associations, funding agencies, and journals due to the recognition that greater accessibility, transparency, and reproducibility ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…As noted earlier, the process of conducting and publishing management research is not “nimble” (Dykes, 2021), and this posed a practical challenge for researchers interested in studying the implications of the pandemic. It is not surprising, then, that the majority of the research that we reviewed was published in the Journal of Applied Psychology , which made a call for papers on the COVID-19 pandemic that included a “rapid review process” (Eby, 2022). It was required that papers submitted as part of this process be short (≤17 pages), and editorial decisions and requested revisions were expedited.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As noted earlier, the process of conducting and publishing management research is not “nimble” (Dykes, 2021), and this posed a practical challenge for researchers interested in studying the implications of the pandemic. It is not surprising, then, that the majority of the research that we reviewed was published in the Journal of Applied Psychology , which made a call for papers on the COVID-19 pandemic that included a “rapid review process” (Eby, 2022). It was required that papers submitted as part of this process be short (≤17 pages), and editorial decisions and requested revisions were expedited.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, our evaluation of this literature is that it is quite rigorous despite the rapid reviews that were used. Indeed, Eby (2022) reported that the acceptance rate for COVID-19 papers at the Journal of Applied Psychology was only 6%, and the articles that we reviewed employed a variety of theoretical perspectives and utilized research designs that were typically methodologically strong, including the use of multiwave/source survey data, archival data, laboratory experiments, field studies, qualitative data, and so on. In some, these methods were combined through the use of multiple studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first of these studies (Sergent & Stajkovic, 2020), published under the “Understanding Work and Employment in COVID-19 Pandemic” heading, appeared in August 2020. The call ultimately generated 828 submissions and 50 published articles (Eby, 2022). In the spirit of transparency and open science, all COVID-related articles published by JAP as a result of this call were free to read through the journal’s website.…”
Section: The Case Of Covid-19 and The Workplacementioning
confidence: 99%
“…Organizational and societal interest in predictive bias and its implications for college admissions, as well as human resource selection and placement, is directly related to ongoing concerns about diversity, equity, and inclusion (DEI), which are considered part of the grand challenges of the 21st century (Eby, 2022; George et al, 2016). Moreover, “historically, testing and assessment has been linked to larger eugenics and white supremacy efforts that have tried to prove, through science, that African Americans and other non-whites are intellectually and culturally inferior” (Davis & Martin, 2018, p. 48).…”
mentioning
confidence: 99%